Basilar impression as complication of Grisel's syndrome. Issue 1 (8th December 2017) - Dührsen, Lasse; Abboud, Tammam; Viezens, Lennart; Eicker, Sven Oliver; Dreimann, Marc
Key Clinical Message: Grisel's syndrome presents a rare disease. Here, we present a peculiar case of Grisel's syndrome with an unfavorable course developing a basilar impression. This highlights the importance of close clinical and radiological follow‐up even in cases where the course seems uncomplicated. Abstract : Grisel's syndrome presents a rare disease. Here, we present a peculiar case of Grisel's syndrome with an unfavorable course developing a basilar impression. This highlights the importance of close clinical and radiological follow‐up even in cases where the course seems uncomplicated.